Nissan's emission control systems to meet Japanese automotive emissions standards. (5th August 2014) - Onoda, M.
The Nissan Motor Company introduced the Nissan Anti–Pollution System (NAPS) in 1975 in response to a tightening of the Japanese emission control standards. The more stringent standards of 1978, requiring an NOx reduction of at least 80%, made a further improvement of NAPS necessary. To effect this improvement Nissan carried out a series of studies. The stabilisation of combustion and the effective induction of heavy exhaust gas re–circulation (EGR) were studied with the aim of reducing NOx with a heavy EGR. A study of a three–way catalyst system was also made with a view to reducing NOx after emission from the cylinder. As a result of these studies, Nissan's models were equipped with the three most appropriate NAPS systems. These systems are described.